1995
DOI: 10.3181/00379727-208-43831
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Specific 17 -Hydroxysteroid Oxidoreductase Type 1 (E.C. 1.1.1.62) as a Possible Target for the Action of Phytoestrogens

Abstract: Several plant estrogens, especially coumestrol and genistein, were found to reduce the conversion of [3H]estrone to [3H] 17 beta-estradiol catalyzed by estrogen-specific 17 beta-hydroxysteroid oxidoreductase Type 1 (E.C. 1.1.1.62) in vitro. Coumestrol, the most potent inhibitor in our experiments, is the best inhibitor of the enzyme known to date. All compounds with inhibitory effects were also estrogenic. However, structural demands for 17 beta-HSOR Type 1 inhibition and estrogenicity of tested compounds in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 16 publications
(23 reference statements)
0
52
1
2
Order By: Relevance
“…On the other hand, the inter-conversion of testosterone to androstenedione is regulated by the activity of 17 -hydroxysteroid dehydrogenase, an enzyme that has been shown to be influenced by phytoestrogens (Makela et al 1995b). Changes in plasma androstenedione levels with the Phyto-600 diet were much lower compared with those observed for testosterone by dietary treatments, suggesting that the substrate supply or enzyme regulation for testosterone synthesis may be affected by the phytoestrogen-rich diet.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, the inter-conversion of testosterone to androstenedione is regulated by the activity of 17 -hydroxysteroid dehydrogenase, an enzyme that has been shown to be influenced by phytoestrogens (Makela et al 1995b). Changes in plasma androstenedione levels with the Phyto-600 diet were much lower compared with those observed for testosterone by dietary treatments, suggesting that the substrate supply or enzyme regulation for testosterone synthesis may be affected by the phytoestrogen-rich diet.…”
Section: Discussionmentioning
confidence: 81%
“…Micromolar concentrations are required for lignan and isoflavone binding to SHBG (5-50 µM) (38) and α-fetoprotein (K d : 0.5-5 µM) (57,58). Concentrations required for inhibition of most steroid metabolizing enzymes are generally in the micromolar range, with the exception 17β-hydroxysteroid dehydrogenase type I, which is inhibited by isoflavonoids at concentrations ranging from 120 nM to 1 µM (33,59).…”
Section: Phytoestrogen Potencies and Active Concentrationsmentioning
confidence: 99%
“…A variety of in vitro assays have now shown that isoflavones and lignans are inhibitors of aromatase (30,31) and 5α-reductase (32). A number of phytoestrogens also inhibit 17β-hydroxysteroid dehydrogenase Type I (33).…”
Section: Hormone Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…(1) increase of serum levels of sex hormone-binding globulin (SHBG) (Adlercreutz et al, 1991;Mousavi and Adlercreutz, 1993); (2) downregulation of enzymes involved in oestrogen biosynthesis, such as aromatase ; (3) inhibition of 17b-hydroxysteroid dehydrogenase type I (Makela et al, 1995); (4) suppression of the gonadotorpins follicule stimulating hormone (FSH) and luteinising hormone (LH); (5) change in intestinal flora, which affect reabsorption of E2 and lower circulating oestrogen levels (Adlercreutz, 1998). Studies examining the effect of a soy protein diet on the menstrual cycle have demonstrated a significant increase in follicular phase length and delay in menstruation, including suppression of midcycle surges of LH and FSH, which potentially may reduce the risk of breast cancer (Cassidy et al, 1994;Lu et al, 1996;Nagata et al, 1998;Kumar et al, 2002).…”
Section: Premenopausal Womenmentioning
confidence: 99%